[All work and no play; Nang magdusa and manunulat; Smokey Mountain - Lazaro, Cheche; Smokey Mountain (Quezon City Probe Productions, 1990)
Children who are forced to work at their young age to augment the familyincome; the screen writers who claimed to augment the family income; the screen writers who claimed to be the most abused and least paid in movie industry; and a singing group named Smokey Mountain discovered by Ryan Cayabyab.
All work and no play (17 min.) -- Nang magdusa and manunulat (14 min.) -- Smokey Mountain (9 min.).
VHS.
Keywords: Street children -- Children -- Employment -- Philippines -- Manila Metropolitan area -- Philippines; Screenwriters -- Philippines